Students’ perceptions of online biology lab activity - Teruk, Kamaril Azlah; Mohd Nasohah, Nor Sa'adah; Ng Ban Choi, Muhammad Ng Chee Hong; Zubir, Nazira (Centre of Foundation Studies, International Islamic University Malaysia, 2023)
The chi-square test is a new experiment introduced during ERTL and the laboratory activity was replaced with a web-based activity. A quantitative survey was conducted on 231 Biological Science students at CFS IIUM by convenience sampling to explore students’ perceptions of the learning activity designed for the chi-square experiment and to explore students’ satisfaction in conducting the online experiment. The students were required to take Biology 1 course, which is one of the core courses for the Biological Science Module. The data from the surveys were analysed by SPSS 26. Mann-Whitney test has demonstrated that learning satisfaction and working in groups assisted female students to comprehend the chi-square test greater than male students, U=2900.5, p=.041 and U=2816, p=.031. On the other hand, for the perception of the ability to create a null hypothesis, the Kruskal-Wallis test indicated a significant difference between students of the Bioscience and Medical Foundation programme, H(5)=14.530, p=0.013. There was no other significant difference in students’ perception and satisfaction when comparing different gender or programmes. The survey showed that all students who participated in the study strongly believed that they understood the Mendel simulation, and were able to create a null hypothesis and perform chi-square test without assistance from the facilitator. In addition, they strongly agree that working in groups contributed to gaining a better understanding of the online experiment. They also expressed satisfaction with the lecturer’s explanation. In conclusion, students were incredibly satisfied with the online experiment. Even though students perceived the experiment positively, it does not imply their ‘actual learning’. Hence, more research is required to evaluate and consolidate the experiment and students’ learning abilities